1993
DOI: 10.1139/x93-262
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to seedling growth in a boreal Scots pine stand: a spatial analysis of a vegetation–soil system

Abstract: The spatial structure of vegetation and soil properties of a patchy Scots pine (Pinussylvestris L.) forest of 1 ha was described and examined in relation to the height growth of pine seedlings in the understory. Measured ecosystem properties included the distribution and sizes of canopy trees, within-stand radiation regime, composition of understory vegetation, and topsoil and mineral soil properties. The joint distance dependent effects of large trees were described as the influence potential, derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 0 publications
3
58
0
6
Order By: Relevance
“…It has been reported that shrub species affect Scots pine regeneration [19]. Although spatial heterogeneity [24] and an efficient dispersal strategy [14] have been suggested as possible explanations for height growth in Scots pine, interspecific competition can also explain the multicohort stand dynamic found in Scots pine stands [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that shrub species affect Scots pine regeneration [19]. Although spatial heterogeneity [24] and an efficient dispersal strategy [14] have been suggested as possible explanations for height growth in Scots pine, interspecific competition can also explain the multicohort stand dynamic found in Scots pine stands [19].…”
Section: Discussionmentioning
confidence: 99%
“…Large trees suppress seedlings and saplings by restricting the availability of nutrients, light and moisture (Kalela, 1942;Kuuluvainen et al, 1993;Kuuluvainen, 1994). However, tree roots may be unevenly distributed and some may have a low vigour (Laitakari, 1927).…”
Section: The Supply and Favourability Of The Microhabitatsmentioning
confidence: 99%
“…The establishment of new seedlings in the stands may be caused by the loss of vitality and death of shrubs, grasses and other tree seedlings due to the effect of drought in dry years. The variation in height growth of Scots pine seedlings has been suggested to be caused mostly by the spatial heterogeneity of the stand [21]. Differences in microsite variables affecting height growth could explain the possibility of promotion of later settlers to the dominant stratum.…”
Section: Population Structure Of Natural Regenerationmentioning
confidence: 99%